2015
DOI: 10.3904/kjim.2016.31.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between metabolic syndrome and thyroid nodules in healthy Koreans

Abstract: Background/Aims:This study evaluated the relationship between thyroid nodules and metabolic syndrome (MS) and its components in apparently healthy Koreans.Methods:We reviewed the records of 3,298 subjects with no noticeable symptoms who underwent thyroid ultrasound imaging as part of a routine check-up between July 2009 and June 2010; of these, 1,308 were excluded based upon predefined criteria. Among the remaining 1,990 patients, we examined the association between MS and its components and the incidence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
56
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 38 publications
11
56
2
3
Order By: Relevance
“… 43 Large BMI was associated with nodule growth among older patients with multiple nodules and larger dominant nodules. 17 A study conducted by Shin et al linked thyroid nodular disease to WC for males and glycated haemoglobin for females, 44 suggesting potential sex disparity. The presence of insulin resistance was associated with larger thyroid gland volume and an increased prevalence of TNs, 45 46 which might be explained by obesity-related subclinical inflammation and an associated increase in levels of insulin-like growth factor-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 Large BMI was associated with nodule growth among older patients with multiple nodules and larger dominant nodules. 17 A study conducted by Shin et al linked thyroid nodular disease to WC for males and glycated haemoglobin for females, 44 suggesting potential sex disparity. The presence of insulin resistance was associated with larger thyroid gland volume and an increased prevalence of TNs, 45 46 which might be explained by obesity-related subclinical inflammation and an associated increase in levels of insulin-like growth factor-1.…”
Section: Discussionmentioning
confidence: 99%
“… 11–15 The recent increase in TNs and thyroid cancer may partly be due to the epidemic of obesity. 9 16 17 Elevated thyroid-stimulating hormone levels and declined free thyroxin (FT4) levels have been observed in obese patients. 16 However, previous studies of the associations between obesity and thyroid were mainly conducted in adults, and the results were not entirely consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Although most thyroid nodules are benign, detecting them early is important because there is always risk that the nodules may be cancerous [ 1 ]. Several factors have been associated with the formation of thyroid nodules, including gender [ 2 4 ], age [ 2 9 ], thyroid-stimulating hormone (TSH) [ 9 ], and iodine intake [ 10 , 11 ]. Numerous studies have also associated thyroid nodules with adiposity [ 3 5 , 8 , 9 , 12 14 ], which is traditionally evaluated based on body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance (IR) was also shown to promote the formation and growth of TN [ 11 ]. Recently, it has been suggested that metabolic syndrome (MetS) was associated with the functional and morphological alterations of the thyroid gland and may be involved in the pathogenesis of TN [ 12 , 13 ]. Although the metabolic risk factors such as obesity, insulin resistance, and abnormal glucose metabolism are involved in the pathogenesis of TN in patients and these have been targeted for therapeutic intervention [ 14 , 15 ], however, up to now, the metabolic mechanisms facilitating TN in individuals still have not been fully investigated, but also there has been scarce literature investigating the different levels of MetS risk factors in subjects with or without TN.…”
Section: Introductionmentioning
confidence: 99%